الأمر في معناه غير الحقيقي في كتاب المستدرك على الصحيحين للحاكم النيسابوري-الأمر للدعاء أنموذجا: The Non-Literal Meaning of the Imperative in Al-Mustadrak ʿalā al-Ṣaḥīḥayn: The Imperative of Supplication as a Model (Khairulummah, 2025)
This study examines the non-literal meaning of the imperative in al-Mustadrak ʿalā al-Ṣaḥīḥayn by al-Ḥākim al-Nīsābūrī, focusing specifically on one of its most prominent figurative uses: the imperative that expresses supplication (duʿāʾ).The research demonstrates that the imperative form in supplications and devotional texts found in al-Mustadrak does not retain its original meaning of command or obligation. Instead, contextual clues convert it into a meaning of humble invocation, since the addressee is God and the verbs used—such as forgive, have mercy, grant sustenance, save us—cannot logically convey authoritative command.The study presents several examples of Prophetic supplications in which the imperative serves the function of prayer, including invocations for forgiveness, guidance, protection, and communal well-being. It also highlights the rhetorical value of this usage, such as its brevity, emotional intensity, expression of devotion, and rhythmic harmony within supplicatory discourse.The research concludes that the imperative used for supplication is one of the most significant figurative meanings of the imperative in Hadith texts, and it is especially prevalent in al-Mustadrak due to the devotional nature of many of its narrations.